Detecting slow introgression of invasive alleles in an extensively restocked game bird - Sanchez-Donoso, Ines; Huisman, Jisca; Echegaray, Jorge; Puigcerver, Manel; Rodríguez-Teijeiro, José D.; Hailer, Frank; Vilà, Carles (Frontiers in Ecology and Evolution, 2014)
Interbreeding of two species in the wild implies introgression of alleles from one species into the other only when admixed individuals survive and successfully backcross with the parental species. Consequently, estimating the proportion of first generation hybrids in a population may not inform about the evolutionary impact of hybridization. Samples obtained over a long time span may offer a more accurate view of the spreading of introgressed alleles in a species’ gene pool. Common quail (Coturnix coturnix) populations in Europe have been restocked extensively with farm quails of hybrid origin (crosses with Japanese quails, C. japonica). We genetically monitored a common quail population over 15 years to investigate whether genetic introgression is occurring and used simulations to investigate our power to detect it. Our results revealed that some introgression has occurred, but we did not observe a significant increase over time in the proportion of admixed individuals. However, simulations showed that the degree of admixture may be larger than anticipated due to the limited power of analyses over a short time span, and that observed data was compatible with a low rate of introgression, probably resulting from reduced fitness of admixed individuals. Simulations predicted this could result in extensive admixture in the near future.